2002
DOI: 10.1007/pl00013093
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Two Races of Phialophora gregata f. sp. adzukicola, Causal Agent of Brown Stem Rot of Adzuki Bean, and Their Genetic Diversity on Hokkaido, Northernmost Island of Japan

Abstract: The distribution of two races (1 and 2) of Phialophora gregata f. sp. adzukicola, the causal agent of brown stem rot of adzuki bean, was examined using a total of 483 isolates obtained from 39 fields in 19 locations on Hokkaido, Japan between 1997 and 1999. Race 1 was predominant (416 isolates or 86.1%) in the commercial fields tested. Race 2 was found in 26 fields (64.1%), including two fields of cultivar Kita-no-otome (resistant to race 1, but susceptible to race 2), indicating that race 2 was widely distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This result may indicate that it requires less than three successive years of cultivation of compatible cultivars for the inoculum potential to be sufficient to cause BSR at the initial density (presumably < 10 3 cfu/g dry soil). Similarly, when cultivating Kita-no-otome in the same soil, the high incidence of BSR and the rapid increase in the frequency of the compatible race (approximately 100% of race 2 isolates) were observed (unpublished data), a All isolates were obtained from 1997 to 1999 b Isolates correspond to race 1 isolates described by Kondo et al (2002), Fig. 2 and were included in the number of isolates probably as a result of the initial high inoculum density of race 2 (> 3 ¥ 10 3 cfu/g dry soil).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This result may indicate that it requires less than three successive years of cultivation of compatible cultivars for the inoculum potential to be sufficient to cause BSR at the initial density (presumably < 10 3 cfu/g dry soil). Similarly, when cultivating Kita-no-otome in the same soil, the high incidence of BSR and the rapid increase in the frequency of the compatible race (approximately 100% of race 2 isolates) were observed (unpublished data), a All isolates were obtained from 1997 to 1999 b Isolates correspond to race 1 isolates described by Kondo et al (2002), Fig. 2 and were included in the number of isolates probably as a result of the initial high inoculum density of race 2 (> 3 ¥ 10 3 cfu/g dry soil).…”
mentioning
confidence: 94%
“…Plants with a DSI of 0 were rated resistant; plants with 0 < DSI < 1.0 were regarded as intermediate (slightly susceptible); and plants with a DSI ≥ 1.0 were considered susceptible. Isolates T649 and T650 from (Kobayashi et al 1981;Kondo et al 2002) c Races were identified (pathogenicity test) using three differential cultivars: Erimo-shozu, Kitano-otome, and Acc259 diseased Acc259 plants were virulent to Erimo-shozu, Hatsune-shozu, and Acc259 but avirulent to Kita-nootome, Syumari, and Acc2515. Consequently, a new race of P. gregata f. sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The multiple resistance of adzuki bean cultivars Kita-no-otome and Syumari has contributed greatly to the control of the two diseases, especially of AFW (Fujita et al 1995Kondo et al 1998Kondo et al , 2002. Although race 2 of BSR, that is virulent to these two cultivars, was discovered in 1995 (Kondo et al 1998, several cultivated and wild adzuki bean accessions resistant to both races 1 and 2 of BSR were selected as potential sources of BSR resistance for breeding programs ).…”
mentioning
confidence: 99%
“…Race 2 isolates were widely distributed in most of the production areas (25 fields, 64.1%) and were sympatric with race 1 isolates in most fields surveyed (Kondo et al 2002), although the frequency of Kondo N. 5 isolation was lower than for race 1.…”
Section: Brown Stem Rotmentioning
confidence: 91%